Além das aparências (ModaPalavra e-periódico, 2017)
The purpose of this article is to describe the importance of appearance in the field of disability, and emphasize how the clothing appears as body language, which not only relates to protection of the individual, but also as a challenge in the social reality of people with disabilities. The review of a stylistic literature it appears that the world stereotypical body image is a striking element and is directly related to a desire to boast, in this case the clothing acts, for people with special needs, as a strategy to accept differentiate and include socially.
Keywords: appearance; disable; clothes